The tripeptide feG inhibits leukocyte adhesion - Davison Joseph S; Christie Emily; Mathison Ronald D (BMC, 2008)
Abstract Background The tripeptide feG (D-Phe-D-Glu-Gly) is a potent anti-inflammatory peptide that reduces the severity of type I immediate hypersensitivity reactions, and inhibits neutrophil chemotaxis and adhesion to tissues. feG also reduces the expression of β1-integrin on circulating neutrophils, but the counter ligands involved in the anti-adhesive actions of the peptide are not known. In this study the effects of feG on the adhesion of rat peritoneal leukocytes and extravasated neutrophils to several different integrin selective substrates were evaluated. Results The adhesion of peritoneal leukocytes and extravasated neutrophils from rats to adhesive proteins coated to 96-well plates was dependent upon magnesium (Mg2+) ion, suggestive of integrin-mediated adhesion. feG inhibited leukocyte adhesion, but only if the cells were stimulated with PAF (10-9M), indicating that feG's actions in vitro require cell activation. In the dose range of 10-10M to 10-12M feG inhibited the adhesion of peritoneal leukocytes to fibrinogen and fibronectin, but not IgG, vitronectin or ICAM-1. feG inhibited the binding of extravasated neutrophils to heparin, IgG, fibronectin and CD16 antibody. Antigen-challenge of sensitized rats reduced the adhesion of peritoneal leukocytes to most substrates and abolished the inhibitory effects of feG. However, pretreating the animals with intraperitoneal feG (100 μg/kg) 18 h before collecting the cells from the antigen-challenged animal restored the inhibition of adhesion by in vitro feG of peritoneal leukocytes and extravasated neutrophils to fibronectin. Conclusion The modulation of leukocyte adhesion by feG appears to involve actions on αMβ2 integrin, with a possible interaction with the low affinity FcγRIII receptor (CD16). The modulation of cell adhesion by feG is dual in nature. When administered in vivo, feG prevents inflammation-induced reductions in cell adhesion, as well as restoring its inhibitory effect in vitro. The mechanism by which in vivo treatment with feG exerts these effects remains to be elucidated.